Prediction models of school-based management, teaching behavior and professionalism - Taguines, Agnes Arceo (2005)
The major thrust of this study was to explore prediction models of school-based management, teaching behavior and professionalism. Serving as respondents were 79 principals from public and private elementary schools in the Division of Tarlac and 375 teachers. Two sets of researcher-made questionnaires were utilized in gathering the needed data. It was found that both public and private school principals practice school-based management but as key figures in this school reform, they focus their efforts more on the organizational conditions of the school than on ways to improve student performance.